Genomic regions associated with embryonic loss in primiparous Holstein cows - Kelson, Victoria C.; Kiser, Jennifer N.; Davenport, Kimberly M.; Suarez, Emaly M.; Murdoch, Brenda M.; Neibergs, Holly L. (Frontiers in Animal Science, 2024)
Reproductive efficiency in dairy cattle bred by artificial insemination (AI) or that are embryo transfer (ET) recipients is important as a means of facilitating the rate of genetic improvement by utilizing superior genetics from sires and donor dams. Fertility is especially challenging in primiparous cows, as they have recently calved, are still growing and are lactating. Fertility, measured by conception rate to the first service (CCR1) is the number of cows that become pregnant to the first AI or ET compared to all cows serviced, whereas times bred (TBRD) is the number of times bred by AI needed to achieve a successful pregnancy. This study aimed to identify loci associated and gene sets enriched for CCR1 in primiparous cows that were bred by AI (n = 882) or were ET recipients (n = 353), and to identify loci associated with TBRD (n= 1851) in primiparous cows. A genome-wide association analysis and gene set enrichment analysis were performed using SNP data for CCR1 and TBRD in primiparous cows. In cows bred by AI, two loci containing five positional candidate genes were associated (p < 1 × 10 -5 ) and one gene set with 18 leading edge genes was enriched (NES ≥3) with CCR1. In cows that were ET recipients, five loci were associated with CCR1, but no gene sets were enriched for CCR1. For the second phenotype, five loci with nine positional candidate genes were associated, and two gene sets with eight leading edge genes were enriched for TBRD. Identifying loci associated or gene sets enriched for CCR1 and TBRD provides an opportunity to better understand embryonic loss in AI bred and ET recipient cows and to use this information to select for higher reproductive efficiency.